Sonoelectrochemical production of hydrogen peroxide at polished boron-doped diamond electrodes - Compton, R; Marken, F; Goeting, C; McKeown, R; Foord, J; Scarsbrook, G; Sussmann, R; Whitehead, A (1998)
Power ultrasound applied to erosion resistant and mechanically stable free standing highly boron-doped diamond electrodes allows the electrochemical reduction of dioxygen to hydrogen peroxide under conditions of extremely high rates of mass transport and in the presence of cavitation.